Stem and Bioentrepreneurship Oriented Project Learning Model to Improve the Senior High Schooll Students’ Soft Skills, Entrepreneurial Interest and Learning Outcome - Latif, Abdul; Saptono, Sigit; Retnoningsih, Amin (Journal of Innovative Science Education)
Soft skills and entrepreneurial interest are kinds of skills that must be owned by the students to face Indonesian demographic peak bonus (2020-2035). The objective of this research was to analyze the students’ soft skills improvement, entrepreneurial interest and learning outcomes by STEM and bioentrepreneurship oriented project learning model implementation. The method of this research used quasi experimental design with the form one group pretest and post test design. The subjects of this research was tenth grade of SMA Negeri 1 Wedung with the total students was 64. The instruments used were questionnaire and test. The questionnaire was used to measure the students’ soft skills and entrepreneurial interest meanwhile the test was used to measure the studens’ learning outcomes. The data analysis technique used criteria standard and N-gain. Criteria standard was to measure the soft skills and entrepreneurial interest meanwhile the N-gain was used to measure the improvement of learning outcomes. The result of the research found that average percentage score of students’ soft skills of X MIPA 1 and X MIPA 2 in high category, it was 71,19% meanwhile percentage score of entrepreneurial interest in category of high enough, it was 60%. The average of index gain the students of experiment class was 0,6382 it meant experiment class had high improvement of learning outcomes. It could be concluded that the implementation of STEM and bioentrepreneurship oriented project learning model could improve soft skills, entrepreneurial interest and learning outcomes of tenth grade students of SMA Negeri 1 Wedung Kabupaten Demak.